Divergence in sink contributions to population persistence - Heinrichs, Julie A.; Lawler, Joshua J.; Schumaker, Nathan H.; Wilsey, Chad B.; Bender, Darren J. (Conservation biology, 2015)
Population sinks present unique conservation challenges. The loss of individuals in sinks can compromise persistence; but conversely, sinks can improve viability by improving connectivity and facilitating the recolonization of vacant sources. To assess the contribution of sinks to regional population persistence of declining populations, we simulated source-sink dynamics for 3 very different endangered species: Black-capped Vireos (Vireo atricapilla) at Fort Hood, Texas, Ord's kangaroo rats (Dipodomys ordii) in Alberta, and Northern Spotted Owls (Strix occidentalis caurina) in the northwestern United States. We used empirical data from these case studies to parameterize spatially explicit individual-based models. We then used the models to quantify population abundance and persistence with and without long-term sinks. The contributions of sink habitats varied widely. Sinks were detrimental, particularly when they functioned as strong sinks with few emigrants in declining populations (e.g., Alberta's Ord's kangaroo rat) and benign in robust populations (e.g., Black-capped Vireos) when Brown-headed Cowbird (Molothrus ater) parasitism was controlled. Sinks, including ecological traps, were also crucial in delaying declines when there were few sources (e.g., in Black-capped Vireo populations with no Cowbird control). Sink contributions were also nuanced. For example, sinks that supported large, variable populations were subject to greater extinction risk (e.g., Northern Spotted Owls). In each of our case studies, new context-dependent sinks emerged, underscoring the dynamic nature of sources and sinks and the need for frequent re-assessment. Our results imply that management actions based on assumptions that sink habitats are generally harmful or helpful risk undermining conservation efforts for declining populations. Los vertederos poblacionales son retos de conservación únicos. La pérdida de individuos en los vertederos puede comprometer la persistencia, pero en contraste, los vertederos pueden aumentar la viabilidad al mejorar la conectividad y al facilitar la recolonización de las fuentes vacantes. Para evaluar la contribución de los vertederos a la persistencia poblacional de las poblaciones declinantes simulamos las dinámicas de fuente-vertedero de tres especies en peligro muy diferentes: el víreo de cabeza negra (Vireo atricapilla) en Fort Hood, Texas; la rata canguro de Ord (Dipodomys ordii) en Alberta; y el búho moteado del norte (Strix occidentalis caurina) en el noroeste de los Estados Unidos. Usamos datos empíricos de estos estudios de caso para hacer parámetros para los modelos espacialmente explícitos basados en individuos. Después utilizamos los modelos para cuantificar la abundancia y la persistencia poblacional con y sin los vertederos a largo plazo. Las contribuciones de los hábitats vertedero variaron ampliamente. Los vertederos fueron dañinos, particularmente cuando funcionaron como vertederos de hoyo negro, para las poblaciones declinantes (p. ej.: la rata canguro) y benignos para las poblaciones robustas (p. ej.: los víreos) cuando se controló en parasitismo del tordo de cabeza café (Molothrus ater). Las contribuciones de vertedero también estuvieron matizadas. Por ejemplo, los vertederos que mantuvieron poblaciones grandes y variables estuvieron sujetos a mayores riesgos de extinción (p. ej.: los búhos moteados). En cada uno de nuestros estudios de caso surgieron vertederos nuevos dependientes del contexto, lo que enfatiza la naturaleza dinámica de nuestras fuentes y vertederos y la necesidad de una reevaluación frecuente. Nuestros resultados implican que las acciones de manejo con base en la suposición de que los hábitats vertedero son generalmente dañinos o útiles corren el riesgo de debilitar los esfuerzos de conservación para las poblaciones declinantes.